SOCIODEMOGRAPHIC FACTORS AND SELF-PERCEIVED MENTAL BALANCE AMONG MEN INCARCERATED FOR SEXUAL CRIMES - Bastos, Claudia Regina Biancato; Gonçalves, Ana Laura de Souza; Dobzinski, Amanda Myrianne; Takano, Nicole Mayumi Carneiro; Schiochet, Gabriela Fernanda; Fadel, Gabrielly Hneda; Fadel, Cristina Berger (Seven Editora, 2026)
Considering that men deprived of liberty for sexual crimes are exposed to multiple psychosocial vulnerability factors, such as stigmatization, fragile social bonds, and limitations in access to care actions, it becomes relevant to investigate the self-perception of mental health in this context. This study aims to analyze the self-perception of mental balance among men incarcerated for sexual crimes, associating it with sociodemographic and prison-related characteristics, such as educational level, prison status, participation in activities, and family support. To this end, an exploratory, descriptive, and analytical study with a quantitative approach was conducted with 90 men deprived of liberty in a prison unit in southern Brazil. Data were collected through a structured questionnaire and analyzed using descriptive and inferential statistics, applying the chi-square test and linear trend analysis, with a 5% significance level. Thus, a high prevalence of very negative self-perception of mental health was observed, especially among individuals in pretrial detention and those with lower educational levels. A significant association was also found between participation in activities and better mental balance, as well as a lower frequency of death-related thoughts. These findings allow the conclusion that contextual and institutional factors, such as access to activities and the definition of legal status, exert a relevant influence on mental health in prison, reinforcing the need for intersectoral strategies to promote mental health in the prison system. DOI: https://doi.org/10.56238/sevened2026.008-012